Pergulatan Perempuan dalam Revolusi Fisik di Bali - Sukiada, I Nyoman; Girindra Wardani, Anak Agung Ayu; Sri Rahayu, Ni Wayan (Humanis, 2021)
This study discusses the role of women in the Physical Revolution in Bali. The appearance of a woman in the history of politics in Bali as a leader has been seen since ancient Balinese times. However, the rise of women seems to have only been seen when the government established the Shanti Girls School. Armed with knowledge and experience in the field of organization, Balinese women are aware of the importance and meaning of independence for a nation. When the Dutch colonial government and NICA troops returned to occupy Bali in March 1946, women played a very important role in defending the independence of the Republic of Indonesia. Women played various roles, such as in the logistics sector as a member of the soup kitchen in charge of providing various types of food to the fighters; in the health sector by helping fighters who were injured and also supplying various types of medicine to the fighters; as a liaison in charge of conveying information on the state of the fighters and the state of the enemy to the leader of the fighters.